2016
DOI: 10.1155/2016/9796768
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intrapleural Tissue Plasminogen Activator and DNase during Extended Use in Complicated Pleural Space Infections

Abstract: The use of intrapleural therapy with tissue plasminogen activator and DNase improves outcomes in patients with complicated pleural space infections. However, little data exists for the use of combination intrapleural therapy after the initial dosing period of six doses. We sought to describe the safety profile and outcomes of intrapleural therapy beyond this standard dosing. A retrospective review of patients receiving intrapleural therapy with tissue plasminogen activator and DNase was performed at two instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
4
24
1
Order By: Relevance
“…There is conflicting data as to whether reducing the dose of tPA will lead to a reduction in pleural bleeding [14,15]. Conversely, a study utilizing extended tPA/DNase dosing (mean 9.8 doses) in patients who were not surgical candidates, demonstrated a similar efficacy rate as six doses but a higher pleural bleeding rate at 10% [16]. Two studies investigated the effect of concurrent administration of tPA and DNase.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting data as to whether reducing the dose of tPA will lead to a reduction in pleural bleeding [14,15]. Conversely, a study utilizing extended tPA/DNase dosing (mean 9.8 doses) in patients who were not surgical candidates, demonstrated a similar efficacy rate as six doses but a higher pleural bleeding rate at 10% [16]. Two studies investigated the effect of concurrent administration of tPA and DNase.…”
Section: Discussionmentioning
confidence: 99%
“…8 Kheir corroborated this concurrent administration of tPA and DNase as a safe and effective option. 9 A study by McClune et al 10 showed that extended use of this intrapleural therapy was safe and effective for pleural space infections. A series of multinational observational studies 11,12 evaluated the combination of tPA and DNase as a "rescue" intervention for community acquired pneumonia if there was no improvement after 24 hours of treatment with antibiotics and tube thoracostomy.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective comparison of extended tPA and DNase (mean 9.8 doses, range 7-16) versus conventional (<6) doses found similar rates of needing surgery (15 vs. 16%), but nonsignificant trends toward more bleeding (10 vs. 3%), additional tube placement (35 vs. 15%), longer LOS (17 vs. 13 days), and greater need to escalate narcotics (80 vs. 57%). 119 Presumably extended dose patients were less fit for or refused surgery, but it appears that patients unsuccessfully drained after a short course of IPFT benefit more from additional image-guided tubes or surgery than prolonged IPFT dosing.…”
Section: Dosing Of Ipftmentioning
confidence: 99%